Microfacies and Depositional Settings of the Eocene Nisai Formation, Pishin Belt, Pakistan - Abdullah, Abdullah; Mohibullah, Mohibullah; Kasi, Aimal Khan; Alam, Shams ul; Haq, Ejaz ul (Journal of Himalayan Earth Sciences, 2023)
The Eocene Nisai Formation of the Pishin Belt at its type section represents thick carbonate- siliciclastics, deposited in an intermittent sub-basin between Eurasian and Indian plates on the north-western margin of Pakistan. These carbonates contain rich assemblages of Larger Benthic Foraminifera (LBF) (Discocyclina, Operculina, Alveolina, Assilina, milliolids, Nummulites etc.), smaller benthic, planktonic foraminifera and other fossil assemblages such as molluscs, brachiopods, bryozoans, algae etc. Microfacies of the Nisai Formation have been studied using biota along with the lithological characters and sedimentary textures. Eight carbonate microfacies have been recognized representing deposition in an inner ramp to outer ramp settings. The association of abundant Nummulties, Assilina, lenticular Discocyclina and algae along with quartz grains at places represent a mid-ramp setting developed as result of episodic relative sea level fall, enhanced continental weathering and tectonic uplift. Flattened Discocyclina, Operculina, Nummulities, smaller benthic foraminifera, planktonic foraminifer accumulation indicates an outer ramp setting and milliolids contribute shallow marine inner ramp environment.